2011
DOI: 10.1063/1.3582902
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation multijunction solar cells: The promise of II-VI materials

Abstract: High concentration photovoltaic (HCPV) systems offer the highest photovoltaic (PV) conversion efficiencies. Also, as production is beginning to ramp up, HCPV is becoming cost competitive with thin-film poly-CdTe and crystalline Si systems in high solar insolation regions. High solar concentrations, X ∼ 500, are used to increase cell efficiencies and greatly reduce the cell area per unit of incident solar radiation, thereby greatly reducing the cell cost per watt. The monolithic three-junction (3J) solar cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…Nevertheless, research into Cd-based TCOs has recently picked up, mainly in response to the development of high efficiency thin-film solar cells which already contain a significant amount of Cd. [3] Much progress has already been made and doped CdO thin-films with resistivities below 10 −4 Ωcm and visible transparency above 80% can be readily deposited by several techniques. [4,5,6,7,8,9] Practical applications aside, CdO is an excellent material in which to study fundamental physics of degenerate semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, research into Cd-based TCOs has recently picked up, mainly in response to the development of high efficiency thin-film solar cells which already contain a significant amount of Cd. [3] Much progress has already been made and doped CdO thin-films with resistivities below 10 −4 Ωcm and visible transparency above 80% can be readily deposited by several techniques. [4,5,6,7,8,9] Practical applications aside, CdO is an excellent material in which to study fundamental physics of degenerate semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…High-quality low-cost Si substrates with large areas are commercially available and II-VI compound semiconductor materials with wide band-gaps have potential for use in visible-wavelength optoelectronics. Based on successful developments in the infrared sensing and imaging industry, some researchers have proposed the growth of the II-VI compound semiconductor material system, CdZnTe/CdTe, on Si substrates for use in multijunction solar cells [2][3][4][5]. High-quality and uniform CdTe epilayers on Si substrates have been grown by molecular beam epitaxy [4], and their characterizations have shown that the minority carrier lifetime of CdTe epilayers may be insensitive to the structural defects that are induced by the lattice mismatch [4,6,7].…”
mentioning
confidence: 99%
“…This problem is thought to be related with structural defects in the polycrystalline CdTe absorbers and interfaces [3]. In the early 1990s, there was a brief interest in CdTe single crystal solar cell devices [3]. However, solar cell community lost interest in CdTe single crystal solar cells due to high production costs and small area of the suitable substrates.…”
mentioning
confidence: 99%
“…Low solar cell efficiencies of the polycrystalline CdTe based solar cells are correlated with the low open circuit voltages (V oc ). This problem is thought to be related with structural defects in the polycrystalline CdTe absorbers and interfaces [3]. In the early 1990s, there was a brief interest in CdTe single crystal solar cell devices [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation